2017
DOI: 10.1007/s00203-017-1366-1
|View full text |Cite
|
Sign up to set email alerts
|

New advances in exopolysaccharides production of Streptococcus thermophilus

Abstract: Streptococcus thermophilus is the most important thermophilic dairy starter, and is widely used in the dairy industry. Streptococcus thermophilus exopolysaccharides received wide attention over recent decades, because they can improve the properties of the dairy product and confer beneficial health effects. The understanding of the regulatory and biosynthetic mechanisms of EPS will improve the EPS biosynthesis, increase the productivity of EPSs, and develop EPSs with desirable properties. The structure of EPSs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 86 publications
2
54
0
Order By: Relevance
“…This result further confirmed that three S. thermophilus strains have close relationships. In addition, these eps clusters belonged to a common type and were found in some S. thermophilus strains, including ASCC1275, Sfi39, KLDS MS, MN-BM-A02, DGCC7710, C106, KLDS 3.1003, TH982, FI9186, and MTC310 (Cui et al, 2017). Furthermore, there was also an additional gene unit eps2C-eps2D in the eps clusters of CS5, CS18, and CS20 which could affect the length of the EPS unit.…”
Section: Exopolysaccharide Biosynthesismentioning
confidence: 94%
See 4 more Smart Citations
“…This result further confirmed that three S. thermophilus strains have close relationships. In addition, these eps clusters belonged to a common type and were found in some S. thermophilus strains, including ASCC1275, Sfi39, KLDS MS, MN-BM-A02, DGCC7710, C106, KLDS 3.1003, TH982, FI9186, and MTC310 (Cui et al, 2017). Furthermore, there was also an additional gene unit eps2C-eps2D in the eps clusters of CS5, CS18, and CS20 which could affect the length of the EPS unit.…”
Section: Exopolysaccharide Biosynthesismentioning
confidence: 94%
“…(Hols et al, 2005;Cui et al, 2016Cui et al, , 2017. Furthermore, it has been confirmed that S. thermophilus has various health benefits such as antiinflammatory activity, antimicrobial activity, antioxidant activity, as well as immunomodulation (Junjua et al, 2016;Cui et al, 2017;Uriot et al, 2017). These probiotic effects have a close relationship with the biologically active molecules produced by S. thermophilus such as EPS and bacteriocins (Hols et al, 2005;Junjua et al, 2016;Cui et al, 2017;Uriot et al, 2017).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations